Mengenali perspektif historis dan modern accounting - Urip Wardoyo, Dwi; Taris Citra Rahadiansyah, Denna; Shofhah Ayuningtias, Naura; Anggraeni Rahmadiah, Deva; Audia Putri, Stefany (Jurnal Riset Pendidikan Ekonomi, 2023)
Historical and modern perspectives in the field of accounting reflect developments and changes in the way we understand, use and organize financial information over the centuries.This study aims to find out how the development of accounting either from history and modern. The method used is the literatur review. The history of accounting begins with the existence of trade which is growing day by day so that better and moreÂ organized records are needed until the Paciolisâ€™s Ledger appear, then in the 19th century double entry accounting has developed a lot. In the 20th century recording began using computer and when the world recession, modern accounting and accounting principles using the double entry aplicaton which lightened the workload of the finance department. Modern accounting was created because of old accounting, meaning that the two synergize and perfect each other until an effective and efficient accounting system is formed.